1973
DOI: 10.1021/j100637a002
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence induced by crystallization of organic binary mixtures

Abstract: Publication costs assisted by Fuji Photo Film Co. Ltd.A novel series of crystalloluminescent organic materials is discovered. The binary mixture of a nonconjugated ketone and acetonitrile or AvY-dimethylacetamide emits blue-white light pulses on crystallization at 77°K. The experimental conditions for effective emission are described. The experimental facts suggest the excitation mechanism that the emission phenomenon is essentially triboluminescence, brought about by strain energy in the mixed crystal. The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

1973
1973
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…In related studies in the past, it was reported that XTL events sometimes accompanied emission from an impurity other than that from the XTL-active compound itself. , However, in the present experiments, no phosphorescence at all was detected from the NIPCz (λ max ∼ 500 nm) . It is worth noting, furthermore, that Takeda et al investigated XTL from a binary mixture (methylbutyl ketone/dimethylacetamide) doped with oxazole derivatives (POPOP, etc) as a fluorescence sensitizer . In this case, neither fluorescence nor phosphorescence was detected from the oxazole derivative in the XTL spectrum of the binary mixture.…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations
“…In related studies in the past, it was reported that XTL events sometimes accompanied emission from an impurity other than that from the XTL-active compound itself. , However, in the present experiments, no phosphorescence at all was detected from the NIPCz (λ max ∼ 500 nm) . It is worth noting, furthermore, that Takeda et al investigated XTL from a binary mixture (methylbutyl ketone/dimethylacetamide) doped with oxazole derivatives (POPOP, etc) as a fluorescence sensitizer . In this case, neither fluorescence nor phosphorescence was detected from the oxazole derivative in the XTL spectrum of the binary mixture.…”
Section: Resultscontrasting
confidence: 63%
“…16 It is worth noting, furthermore, that Takeda et al investigated XTL from a binary mixture (methylbutyl ketone/dimethylacetamide) doped with oxazole derivatives (POPOP, etc) as a fluorescence sensitizer. 9 In this case, neither fluorescence nor phosphorescence was detected from the oxazole derivative in the XTL spectrum of the binary mixture. Therefore, to the best of our knowledge, this is the first report of fluorescent crystalloluminescence from an organic compound: NIPCz.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Only a limited number of organic and inorganic materials is known to be crystalloluminescent (Barsanti and Maccarrone 1991). The CRL emission may occur due to several processes such as (i) amorphous to crystalline transformation, (ii) polymorphic phase transition, (iii) microfracture of crystallites and (iv) chemical reaction during crystallization (Harvey 1957, Garten and Head 1963, 1966, 1970, Tsuda et al 1939, Walton 1977, Chandra and Zink 1980, Chandra 1982, Takeda et al 1973, Gibbon et al 1988, Barsanti and Maccarrone 1991.…”
Section: Introductionmentioning
confidence: 99%